Impact of Novel Food Processing Techniques on the Physicochemical, Dietary, Sensory, and Safety Characteristics of Plant-Based Non-dairy Drinks - Jaiswal, Harish; Poorti Sharma (Journal of Food Health and Bioenvironmental Science, 2025)
Cow's milk (CM) is a staple in numerous diets due to its comprehensive nutritional profile, providing all essential nutrients required for human health. It is widely consumed as a beverage and incorporated into various culinary applications, including coffee, tea, milkshakes, and a broad range of dairy-based products such as ice cream, curd (or yogurt), cakes, and confections. Nevertheless, CM is not a good option for many people because of the reasons like lactose intolerance, allergies to milk proteins, metabolic diseases (for instance, galactosemia where the body cannot process galactose), and dietary restrictions due to different reasons like veganism, plant-based preferences, or religious and cultural practices that do not allow them to eat dairy products at all. Not only this, but also there have been many discussions on the possible health risks of dairy consumption, such as acne, high saturated fat intake, and cardiovascular disease. Plant-based Milk (PbM) alternatives have come up to satisfy the ever-increasing demand for Non-dairy substitutes that not only visually and texturally resemble CM but also have similar functional properties. These alternatives come with environmental benefits as well, among which is the eco-friendliness of the PbM production chain, and also the reduction of carbon emissions when compared to the dairy industry. However, the nutritional quality of PbM products is very often lower than that of the Plant-based Drinks (PbD) in terms of flavor, texture, and solubility, which makes it very difficult for these products to be accepted by a wider audience and be competitively positioned in the market. The most common method of microbial stability and shelf-life extension is thermal processing, while at the same time, high temperatures may lead to the loss of sensitive chemicals and may also raise specific unfavorable reactions, which result in the decrease of protein digestibility and amino acid bioavailability in Non-dairy PbD alternatives. To address these limitations, innovative non-thermal technologiessuch as high-pressure processing, pulsed electric fields, and ultrasoundare being explored for their potential to enhance product stability, nutrient retention, and sensory appeal without compromising safety. Even though the results from the preliminary stages were very encouraging, studies that were done on these new techniques and their effect on PbD are still very limited. So, research in the future should mainly focus on interdisciplinary cooperation to move forward with the development of PbM products that are suitable for health, nice to eat and drink, and different from each other according to the needs of the consumers.